Radiation-Induced Myelitis: Initial and Follow-Up MRI and Clinical Features in Patients at a Single Tertiary Care Institution during 20 Years - Khan, M.; Ambady, P.; Kimbrough, D.; Shoemaker, T.; Terezakis, S.; Blakeley, J.; Newsome, S.D.; Izbudak, I. (American Journal of Neuroradiology, 2018)
SUMMARY: Myelitis is a rare complication of radiation exposure to the spinal cord and is often a diagnosis of exclusion. A retrospective review of clinical records and serial imaging was performed to identify subjects with documented myelitis and a history of prior radiation. Eleven patients fulfilled the inclusion criteria. All patients had longitudinally extensive cord involvement with homogeneous precontrast T1 hyperintense signal in the adjacent vertebrae, corresponding to the radiation field. T2 signal abnormalities involving the central two-thirds of the cord were seen in 6/11 patients (55%). The degree of cord expansion and contrast enhancement was variable but was seen in 6 (54%) and 5 (45%) patients, respectively. On follow-up, 2 patients developed cord atrophy, while complete resolution was noted in 1. Clinical improvement was noted in 5 patients, with symptom progression in 2 patients. Our results suggest that radiation myelitis is neither universally progressive nor permanent, and some radiographic and clinical improvement may occur.RMradiation myelitis